Transcriptomic and metabolomic analyses reveal the potential mechanism of waterlogging resistance in cotton (Gossypium hirsutum L.) - Owusu, Anane Gideon; Lv, Yin-Ping; Liu, Man; Wu, Yong; Li, Cheng-Lin; Guo, Ning; Li, Da-Hui; Gao, Jun-Shan (Frontiers in Plant Science, 2023)
Introduction Cotton (Gossypium hirsutum L.) is susceptible to long-term waterlogging stress; however, genomic information of cotton response mechanisms toward long days of waterlogging is quite elusive. Methods Here, we combined the transcriptome and metabolome expression level changes in cotton roots after 10 and 20 days of waterlogging stress treatment pertaining to potential resistance mechanisms in two cotton genotypes. Results and discussion Numerous adventitious roots and hypertrophic lenticels were induced in CJ1831056 and CJ1831072. Transcriptome analysis revealed 101,599 differentially expressed genes in cotton roots with higher gene expression after 20 days of stress. Reactive oxygen species (ROS) generating genes, antioxidant enzyme genes, and transcription factor genes (AP2, MYB, WRKY, and bZIP) were highly responsive to waterlogging stress among the two genotypes. Metabolomics results showed higher expressions of stress-resistant metabolites sinapyl alcohol, L-glutamic acid, galactaric acid, glucose 1-phosphate, L-valine, L-asparagine, and melibiose in CJ1831056 than CJ1831072. Differentially expressed metabolites (adenosine, galactaric acid, sinapyl alcohol, L-valine, L-asparagine, and melibiose) significantly correlated with the differentially expressed PRX52, PER1, PER64, and BGLU11 transcripts. This investigation reveals genes for targeted genetic engineering to improve waterlogging stress resistance to enhance abiotic stress regulatory mechanisms in cotton at the transcript and metabolic levels of study.